The role of whole exome sequencing in the UBE3A point mutation of Angelman Syndrome: A case report - Triono, Agung; Iskandar, Kristy; Nugrahanto, Andika Priamas; Hadiyanto, Marissa Leviani; Gunadi, Gunadi; Herini, Elisabeth Siti (Elsevier Ltd, 2022)
Introduction: Angelman Syndrome (AS) is a rare disorder with a relatively well-defined phenotype caused by lack of expression of the maternally inherited ubiquitin-protein ligase E3A (UBE3A) gene in the brain. This article describes the role of genetic testing using whole-exome sequencing (WES) in detecting rare AS variants, a point mutation in the UBE3A gene. Case presentation: We describe a rarely reported clinical presentation of AS in a two year and ten months old girl with severe developmental delay, movement and balance disorder, frequent smiling, apparent happy demeanor, speech impairment, absence of seizure, lack of sleep, and abnormal food-related behavior. Physical examination showed microcephaly, with facial characteristics of AS, ataxia gait, and truncal hypotonia. The electroencephalogram showed medium amplitude rhythmic 2-3c/s. Brain Magnetic Resonance Imaging revealed microcephaly, corpus callosum dysgenesis, and heterotopia grey matter on the bilateral lateral ventricle. WES was conducted to search pathogenic variants and showed a heterozygous mutation in exon 9 of the UBE3A gene, c.1513C > T (p.Arg505Ter). Conclusion: Angelman syndrome is a neurodevelopmental disorder that has several underlying genetic etiologies. WES could detect a rare variant of Angelman syndrome, identified as the point mutation of the UBE3A gene, which cannot be seen with other modalities. © 2021